Quantification of the first-order high-pass filter's influence on the automatic measurements of the electrocardiogram. (February 2017) - Isaksen, Jonas; Leber, Remo; Schmid, Ramun; Schmid, Hans-Jakob; Generali, Gianluca; Abächerli, Roger
Highlights: This study shows a correlation relationship between the QRS integral and the ST-segment deviation. We show significant differences between AC- and DC-coupled ECG recorded signals. As the work is based on clinical digital ECG records stored in raw format, there is an impact for clinicians as well as technicians. However, we also show that in a clinical content, the alterations to the P wave and QRS complex are minor. Abstract: Background and objective: The first-order high-pass filter (AC coupling) has previously been shown to affect the ECG for higher cut-off frequencies. We seek to find a systematic deviation in computer measurements of the electrocardiogram when the AC coupling with a 0.05 Hz first-order high-pass filter is used. Methods: The standard 12-lead electrocardiogram from 1248 patients and the automated measurements of their DC and AC coupled version were used. We expect a large unipolar QRS-complex to produce a deviation in the opposite direction in the ST-segment. Results: We found a strong correlation between the QRS integral and the offset throughout the ST-segment. The coefficient for J amplitude deviation was found to be −0.277 µV/(µV⋅ s). Conclusions: Potential dangerous alterations to the diagnostically important ST-segment were found. Medical professionals and software developers for electrocardiogram interpretation programs should be aware of such high-pass filter effects since they could be misinterpreted as pathophysiology or some pathophysiology could be masked by these effects.